Characteristics of soil nutrients and their relationship with soil microbial properties in Artemisia sacrorum communities in the loess hilly region - Song, Lijuan; Liu, Weiyang; Wu, Huifeng; Gao, Tian; Hao, Wenfang (International Journal of Agricultural and Biological Engineering, 2018)
Artemisia sacrorum communities with different growth years were selected to analyse soil nutrient characteristics, the variation in soil microbial properties, and their relationships in the loess hilly region. The results showed that with an increase in the number of growth years, soil microbial biomass carbon and nitrogen contents as well as soil phosphatase and urease activities initially decreased and then increased in the A. sacrorum communities. The soil organic carbon, organic nitrogen, and total nitrogen contents as well as soil respiration rate showed an increasing trend and reached a maximum at age (a) 37. The soil available phosphorus content first decreased and then increased, with the lowest level observed at 18 a. By contrast, soil available potassium initially increased and then decreased. Soil microbial biomass carbon had a significant positive correlation with soil organic carbon, total nitrogen and organic nitrogen, while soil respiration had a significant positive correlation with organic nitrogen, soil phosphatase and organic carbon. Soil respiration had a highly significant positive correlation with organic carbon and total nitrogen, while soil phosphatase had a highly significant positive correlation with total nitrogen and organic nitrogen. In the A. sacrorum communities, the soil organic carbon and total nitrogen contents were mainly affected by soil respiration, soil available potassium content was mainly affected by soil urease activity, and soil organic nitrogen content was mainly affected by soil phosphatase activity. These findings indicate that soil basal respiration, urease activity and phosphatase activity were the major microbial factors affecting the characteristics of the soil nutrients in the A. sacrorum communities. In conclusion, the natural restoration process of A. sacrorum communities can enhance soil microbial activity and improve soil quality. Keywords: loess hilly, soil nutrients, soil microbial biomass, soil enzyme activities, soil basal respiration rate DOI: 10.25165/j.ijabe.20181104.3942 Citation: Song L J, Liu W Y, Wu H F, Gao T, Hao W F. Characteristics of soil nutrients and their relationship with soil microbial properties in Artemisia sacrorum communities in the loess hilly region. Int J Agric & Biol Eng, 2018; 11(4): 127-134.